IMPACT OF TRUCK DRIVERS' STRIKE ON RISK MANAGEMENT IN SUPPLY CHAINS: THE CASE OF A HOSPITAL IN THE STATE OF MINAS GERAIS: IMPACT OF TRUCK DRIVERS' STRIKE ON RISK MANAGEMENT IN SUPPLY CHAINS: THE CASE OF A HOSPITAL IN THE STATE OF MINAS GERAIS - Barra , Geraldo Magela Jardim; Silva, Rodrigo Oliveira da; Silveira, Rebecca Impelizieri Moura da (Brazilian Journal of Production Engineering, 2020)
This article aims to demonstrate the importance of a risk management plan for supply chain management in the hospital sector. The risk mitigating actions of a hospital were analyzed during the truckers' strike that occurred in May 2018. A single case study was used, approached with a set of evidence collection instruments, both through analysis of the reports of the institution's manager target and document analysis. We opted for content analysis with categories established a priori and concerning the risk management literature in supply chains. The fundamental factor used by the hospital as a mitigation strategy was the quality program with a contingency plan and the hospital's relationship with its relationship networks. The sharing of information between these organizations was essential for the hospital to maintain the quality of the services provided.
Keywords: Supply chain management; truckers strike; risk management in supply chains; contingency plan